Shielding characteristics OF the electromagnetic Shields on the base of Shungite-concrete containing bischofite and calcium chloride - M. S. Mahmoud; E. S. Belousova; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Frequency dependencies of transmission and reflection coefficients of pyramid shields with addition of bischofite and calcium chloride in the frequency range of 0,5…18 GHz are presented.